A Proposal of a Practical and Optimal Prophylactic Strategy for Peritoneal Recurrence. (8th February 2012) - Kuramoto, Masafumi; Shimada, Shinya; Ikeshima, Satoshi; Matsuo, Akinobu; Kuhara, Hiroshi; Eto, Kojiro; Baba, Hideo
Abstract : Peritoneal metastasis, which often arises in patients with advanced gastric cancer, is well known as a miserable and ill-fated disease. Once peritoneal metastasis is formed, it is extremely difficult to defeat. We advocated EIPL (extensive intraoperative peritoneal lavage) as a useful and practical adjuvant surgical technique for those gastric cancer patients who are likely to suffer from peritoneal recurrence. In this paper, we review the effect of EIPL therapy on prevention of peritoneal recurrence on patients with peritoneal free cancer cells without overt peritoneal metastasis (CY+/P−) through the prospective randomized study, and we verified its potential as an optimal and standard prophylactic therapeutic strategy for peritoneal recurrence.